2014
DOI: 10.21977/d910119302
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Professional Development in the Use of Arts-Integrated Activities with Mathematics Content: Findings About Program Implementation

Abstract: In 2010, the Wolf Trap Foundation for the Performing Arts, Institute for Early Learning Through the Arts, was awarded an Arts in Education Model Development and Dissemination (AEMDD) grant to develop, implement, and disseminate a research-based program of professional development (PD) that equips prekindergarten and kindergarten teachers to infuse mathematics instruction with arts instruction in their classrooms. The PD includes summer institutes and classroom-based residencies in which music, dance, and drama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Based on the analysis of coaching procedure, we found two ways of coaching: on‐site coaching ( N = 24, 72.7%) and web‐mediated coaching (or distance coaching, N = 8, 24.2%). Details of the coaching procedure in two studies were unavailable (i.e., Ludwig & Song, 2015; Raver et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis of coaching procedure, we found two ways of coaching: on‐site coaching ( N = 24, 72.7%) and web‐mediated coaching (or distance coaching, N = 8, 24.2%). Details of the coaching procedure in two studies were unavailable (i.e., Ludwig & Song, 2015; Raver et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In Landry et al's (2006) Academic skills Ludwig and Song's (2015) intervention study indicated that the coaching programme had significant positive impact on children's mathematics attainment in the first and the second year of implementation. The positive effect of coaching on children's academic skills should also be linked to their language skills and self-regulation, which are particularly sensitive to teaching quality (Pianta et al, 2017).…”
Section: Social-emotional Developmentmentioning
confidence: 99%
“…Arts-based pedagogies use one or more art forms to stimulate creative processes and deepen understanding in non-arts learning (Lee, Cawthon & Dawson, 2013;Ludwig & Song, 2014). Integration of a range of disciplines with the arts has been shown to have powerful effects on learning.…”
Section: Arts-based Pedagogiesmentioning
confidence: 99%
“…By engaging in experiences that enhance nurses’ awareness of the body’s role in the self, nurses will be better prepared to mindfully care for clients [ 3 , 4 , 20 ]. An arts-integrated pedagogy is a holistic learning approach that incorporates the intersection between the nature (environment) and the embodied practice of the human body, mind, and emotions [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%